Multiobjective H2/H∞ Control Design with Regional Pole Constraints - Hardiansyah Hardiansyah; Junaidi Junaidi (Universitas Ahmad Dahlan, 2012)
This paper presents multiobjective H2/H∞ control design with regional pole constraints. The state feedback gain can be obtained by solving a linear matrix inequality (LMI) feasibility problem that robustly assigns the closed-loop poles in a prescribed LMI region. The proposed technique is illustrated with applications to the design of stabilizer for a typical single-machine infinite-bus (SMIB) power system. The LMI-based control ensures adequate damping for widely varying system operating conditions. The simulation results illustrate the effectiveness and robustness of the proposed stabilizer.